Kinerja Badan Pengawasan Keuangan dan Pembangunan (BPKP) di Provinsi Sulawesi Utara - Siagian, Mery Krismas; Pangkey, Masje; Rares, Joyce (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Finance and Development Superfisory Agency is a non – departmental institution formed only by Presidential decree.Where many people judge needs to be done over the dissolution of theFinance and Development Superfisory Agency,the reason is because it is necessary for both power and efficiency of public spending because it has too many institutions existing internal control. This research is done on the employees of Finance and Development Superfisory Agency in North Sulawesi.Thepuspose of this study was to determine the performance of the Finance adnDevelpoment Supervisory Board role in serving the community. The analytical method used is descriptive method in the from of field that is required in this study is derived from the result of interviews,field notes and photos- photos as a field.Then the fields obtained by researchers, it will be the field using an interpretive approarch,where researchers interpret the meaning of the field that has been collected by giving attention and record as many aspects studied at the time. Keywords : Performance:Finance and Development Superfisory Agency